Readiness of Technical Vocational Institutions in the Delivery of Technical Vocational Education and Training for Differently Abled Persons - Im-motna, Rey (Journal of Interdisciplinary Perspectives, 2025)
Even though inclusive education is getting more attention, we still don’t fully understand how Technical Vocational Institutions (TVIs) in Baguio City run Technical Vocational Education and Training (TVET) programs designed for people with disabilities. Therefore, this study investigated the degree of initiative by Technical Vocational Institutions (TVIs) in Baguio City, whether there was low in-placed initiative based on the inclusion criteria, or whether the institution already showed a great degree of initiative. The study then intends to investigate additional factors influencing education inclusion. The study uses a modified and validated survey questionnaire in a mixed-method research design that is anchored in the Vocational Education and Training (VET) toolbox criteria, which consist of five (5) major indicators: Disability Support Unit (DSU), Accessibility, Human Resources, Complaint Mechanism, and Funding for Inclusion. The survey included 12 school heads/administrators with TESDA program registrations in tourism, construction, language, ICT, and health. The research found that most schools lack the initiative and evidence to implement inclusive education. Despite the limited initiative from the institutions, 9 out of the 12 schools adhere positively to some inclusiveness criteria, such as correct designs on doors, gates, stairs, rooms, sanitary conditions, work equipment, and escape and rescue measures. The follow-up interview identifies additional factors influencing the provision of technical training for persons with disabilities (PWD). These factors encompass challenges related to accessibility and infrastructure, financial support and resource limitations, human resource and instructor training, inclusive curriculum and support services, commitment to strategic planning and long-term implementation, attitudinal barriers, and societal stigma. The study recommended establishing a Disability Support Unit (DSU) and dealing with the factors that hinder the full implementation of inclusive education for persons with disabilities.